The Significance of Redox Biomarkers in the Evaluation of the Antioxidant Profile In Vitro and In Vivo - Aristidis S. Veskoukis; Periklis Vardakas; Dimitrios Kouretas (MDPI AG, 2021)
The present Special Issue of Antioxidants, entitled The Significance of Redox Biomarkers in the Evaluation of the Antioxidant Profile In Vitro and In Vivo, ten research articles emphasize the significance of adopting reliable redox biomarkers to determine the antioxidant activities of bioactive compounds in vitro and to assess blood and tissue redox status in vivo [...]